Design of helical antenna for next generation wireless communication - Zeain, M.Y. (Wydawnictwo SIGMA-NOT, 2020)
This study proposes a novel helical antenna design for next generation applications. The strip helical antenna is prescribed for next generation wireless communication and wideband applications that offer circular polarization and a wide bandwidth. In fact, the proposed helical antenna suits 5.8 GHz frequency by using Teflon material. The newly-designed strip was printed on a substrate and rolled into a helix shape to achieve circular polarization without impedance matching. This antenna is meant for wideband wireless communication applications. A wide bandwidth of 2.7 GHz with 5.8 GHz resonant frequency was attained through the use of helical antenna on Teflon substrate. The proposed antenna on Teflon substrate recorded a gain of 8.97 dB and 92 efficiency. The antenna design parameters and the simulated results were retrieved using Computer Simulation Technology software (CST). The measurement result of return loss displayed mismatch at 5.22 GHz due to manual fabrication. This developed antenna may be applied for a number of wireless applications, including Wideband, Ultra-wideband, and 5G. Â© 2020 Wydawnictwo SIGMA-NOT. All rights reserved.